Safe patient handling legislation and musculoskeletal disorders among California healthcare workers: Analysis of workers' compensation data, 2007–2016. Issue 7 (17th May 2022) - Lee, Soo‐Jeong; Lee, Joung Hee; Harrison, Robert
Abstract: Background: California requires general acute care hospitals to have a comprehensive plan to prevent patient handling injuries (PHIs) among employees. The California safe patient handling (SPH) law took effect in 2012. This study assessed the impact of the SPH law on workers' compensation claims for musculoskeletal disorders (MSDs) in California hospital workers. Methods: We used California Workers' Compensation Information System data from 2007 to 2016 and analyzed claims for MSDs that occurred in acute care hospitals compared with nursing and residential care facilities. MSD claims were classified into PHI and non‐PHI claims. Results: We identified 199, 547 MSD claims that occurred during 2007–2016 in acute care hospitals (62.8%) and nursing and residential care facilities (37.2%). MSDs accounted for 42.8% of all claims. Of the MSD claims, 81.0% were strains or sprains and 33.5% of MSDs were related to patient handling activities. From 2011 to 2016, MSD claim rates showed significant reductions among both hospital and nursing/residential care workers. However, the MSD‐PHI claim rate showed a significant reduction only among hospital workers (7.3% per year, incidence rate ratio [IRR] = 0.927, 95% confidence interval [CI] 0.903–0.952). There was no significant change among nursing/residential care workers (IRR = 0.990, 95% CI 0.976–1.005). The non‐PHI claim rate showed no significant change among hospital workers (IRR = 0.982, 95% CI 0.956–1.009). Conclusions: Our study identified significant reductions of PHI claims among California hospital workers after the passage of the SPH legislation, suggesting that SPH legislation played a crucial role in reducing the risk of injury among healthcare workers.